Enhancing the interlaminar adhesion of carbon fiber composites via carbon nanotube sheets - Ning Bian; Yao Ren; Ashutosh Shrivastava; Zhong Wang; Duck J. Yang; Samit Roy; Ray Baughman; Hongbing Lu (Academia Materials Science)
Spread tow carbon fiber composites are receiving increased attention for diverse applications in space and sports gear due to their thin form, which is suitable for deployable structures, and high tensile strength. Their compressive strength, however, is much lower than their tensile strength due to low interlaminar strength. Herein we report a facile technique to enhance their performance through interlaminar insertion of aligned carbon nanotube (CNT) sheets. The inserted CNT sheets also provide electrical conductivity in the composites even at a low CNT loading below the electrical percolation threshold established for CNT-filled composites. Mechanical and electrical characterization was conducted on the CNT sheet-inserted composites and the baseline composites. Results show that the CNT sheets increase the compressive strength by 14.7% compared with the baseline. Such an increase is attributed to the increased adhesion provided by the inserted CNT sheets at the interface between neighboring plies, which also increases the interlaminar shear strength by 33.0% and the interfacial mode-II fracture toughness by 34.6% compared with the baseline composites without inserting CNT sheets. The well-aligned CNT sheet structure maintained between the neighboring plies contributed to a 64.7% increase in electrical conductivity compared with the baseline composites. The findings indicate that the insertion of well-aligned ultrathin CNT sheets in the interlaminar region of a spread tow carbon fiber composite provides significant enhancement in mechanical and electrical performance, paving the path toward applications where both mechanical and electrical performances are crucial, such as for structural health monitoring, lightning protection, and de-icing in aircraft and wind blades.